Studi Kasus Tentang Siswa yang Mengalami Kesulitan Belajar Matematika di SMP Negeri 10 Pontianak Tahun Ajaran 2022/2023 - Diba, Putri Vara; Yuline, Yuline; Putri, Amallia (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The aim of this research is to know and deeply analyze the difficulties in learning math for students in SMP Negeri 10 Pontianak. The case subject of this research contains two students from grade VII who find it difficult to learn math. This research uses the descriptive method with a qualitative approach in case study form. The data collecting technique used in this research is the test technique which contains academic achievement tests and non-test techniques which are observation, interview, and documentation. The data analysis technique used study case steps including problem identification, diagnosis, prognosis, treatment, evaluation, and follow-up. In giving treatment, the researcher used the Rational Emotive Behaviour Therapy (REBT) counseling model with different techniques. According to the result of the research, there is a positive change that shows in the subject of case I and the subject of case II after receiving treatment four times. The changes in the subject of the case are paying attention to the teacher, doing tasks or homework, showing a sense of responsibility, being able to manage time, being able to do assertive adaptive to train and familiarize to adapt positively and there is an improvement on academic achievement. The change in the subject of case II shows paying attention to the teacher, doing tasks or homework that was given, being assertive to control emotions, having a sense of responsibility, and the improvement of academic achievement.